2021
DOI: 10.1186/s12885-021-08311-8
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of nasopharyngeal carcinoma at Tikur Anbessa Hospital, Ethiopia

Abstract: Background Nasopharyngeal cancer is distinguished from other cancers of the head and neck in its epidemiology, histopathology, clinical characteristics, and therapeutic outcome. Its unique clinico-epidemiologic pattern of the disease is an area focus for this investigation. Accordingly, the study investigated the demographic and histologic characteristics, as well as the clinical stage at presentation of nasopharyngeal carcinoma patients at Tikur Anbessa Specialized hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…11 The clinical patterns of nasopharyngeal cancers in Ethiopia is consistent with intermediaterisk endemic areas; however, association with EBV has not been confirmed by analysis of tumor viral EBV DNA. 12 In this study, the majority of patients had locally advanced head and neck cancer at diagnosis which is observed in countries of high-and low-resource levels alike. [13][14][15][16] Multiple factors influence the timely diagnosis of cancer in Africa such as cultural beliefs, educational level, transportation, and poverty.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…11 The clinical patterns of nasopharyngeal cancers in Ethiopia is consistent with intermediaterisk endemic areas; however, association with EBV has not been confirmed by analysis of tumor viral EBV DNA. 12 In this study, the majority of patients had locally advanced head and neck cancer at diagnosis which is observed in countries of high-and low-resource levels alike. [13][14][15][16] Multiple factors influence the timely diagnosis of cancer in Africa such as cultural beliefs, educational level, transportation, and poverty.…”
Section: Discussionmentioning
confidence: 69%
“… 11 The clinical patterns of nasopharyngeal cancers in Ethiopia is consistent with intermediate-risk endemic areas; however, association with EBV has not been confirmed by analysis of tumor viral EBV DNA. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the study by Adriana who showed 84.9% of Stage III and IV patients, and the study in Ethiopia showed 86.2%. Studies in endemic areas show 80−90% of Stage III and IV cases [17], [18]. This could indicate the difficulty of early diagnosis due to the vague symptoms that arise in the early stages [19].…”
Section: Discussionmentioning
confidence: 99%
“…The histological types are mostly poorly differentiated or undifferentiated carcinomas. The incidence is high in southern China and North Africa ( Beyene et al, 2021 ; Bossi et al, 2021 ). According to GLOBOCAN ( Bray et al, 2018 ), the incidence in these regions is 4–25 cases per 1,00,000 people, which is 50–100 times higher than the incidence in the rest of the world.…”
Section: Introductionmentioning
confidence: 99%